Mães em luto: narrativas de sofrimento decorrentes do extermínio de jovens em Goiânia - Rosa, Fabrício Silva (2016)
“Mothers in grief: narratives of suffering caused by youth extermination in Goiânia” depicts the results of my forays into the lives of adolescents’ mothers who were murdered meanwhile the accomplishment of socio-educational policies in Goiânia. Based on information from records available in the public body responsible for monitoring youngsters in conflict with the law, along with compelling stories of women in grief, I have tried to comprehend their biographies and discuss motherhood, noticeably those experienced mainly in adversity conditions, moreover their anguish and pain due to conflicts faced by their children. Furthermore, I have examined the role of mothers in caring for their children, not only defending their rights but also organizing social mechanisms to claim them, also the effects of death and the elaboration of mourning in their daily lives. Motherhood, gender, adolescence and grief were made conceptual lenses through which the lives of these women were read. The results demonstrate that the extermination of youngsters is followed by social representations of woman hyper liability in child support amongst feminization contexts of poverty, consolidated in processes of exclusion of the less white youngsters, peripheral and lower access to material goods, crisscrossed with a cruel and violent war against drugs.